Characterization of regulatory dendritic cells differentiated from the bone marrow of UV‐irradiated mice. Issue 4 (28th October 2013) - Ng, Royce L. X.; Scott, Naomi M.; Bisley, Jackie L.; Lambert, Misty J.; Gorman, Shelley; Norval, Mary; Hart, Prue H.
Summary: When antigen‐loaded dendritic cells (DCs) differentiated from the bone marrow (BM) of UV‐irradiated mice (UV‐BMDCs) were adoptively transferred into naive mice or mice pre‐sensitized with that antigen, the recipients exhibited a reduced immune response following antigen challenge. Hence, UV‐BMDCs are poorly immunogenic and can suppress pre‐existing immunity. The UV‐induced effect on BM‐derived DCs was rapid (observed 1 day after UV radiation), long‐lasting (observed 10 days after UV radiation) and UV dose‐dependent. The mechanism by which UV‐BMDCs could regulate immunity was investigated. The CD11c + cells, differentiated using granulocyte–macrophage colony‐stimulating factor + interleukin‐4, were confirmed to be DCs because they did not express the myeloid‐derived suppressor cell marker, Gr1. UV‐BMDCs did not display altered antigen uptake, processing or ability to activate T cells in vitro . When gene expression in UV‐BMDCs and DCs differentiated from the BM of non‐irradiated mice (control‐BMDCs) was examined, Ccl7, Ccl8 and CSF1R ( CD115 ) mRNA transcripts were up‐regulated in UV‐BMDCs compared with control‐BMDCs. However, neutralizing antibodies for Ccl7 and Ccl8 did not abrogate the reduced immunogenicity of UV‐BMDCs in vivo . Moreover, the up‐regulation of CSF1R transcript did not correspond with increased receptor expression on UV‐BMDCs. The phenotypes of UV‐BMDCs and control‐BMDCs were similar, with no difference in the expression of CD4, CD8α, CD103, B220 or F4/80, or the regulatory molecules CCR7 (CD197), FasL (CD95L), B7H3 (CD276) and B7H4. However, PDL1 (CD274) expression was reduced in UV‐BMDCs compared with control‐BMDCs following lipopolysaccharide stimulation. In summary, UV‐BMDCs do not express the classical phenotypic or gene expression properties of DCs reported by others as 'regulatory' or 'tolerogenic'.